Blocking preferential glucose uptake sensitizes liver tumor-initiating cells to glucose restriction and sorafenib treatment. (1st March 2017) - Zhang, Hui-Lu; Wang, Ming-Da; Zhou, Xu; Qin, Chen-Jie; Fu, Gong-Bo; Tang, Liang; Wu, Han; Huang, Shuai; Zhao, Ling-Hao; Zeng, Min; Liu, Jiao; Cao, Dan; et al.
Abstract: Cancer cells display altered metabolic phenotypes characterized by a high level of glycolysis, even under normoxic conditions. Because of a high rate of glycolytic flux and inadequate vascularization, tumor cells often suffer from nutrient deficiency and require metabolic adaptations to address such stresses. Although tumor-initiating cells (T-ICs) have been identified in various malignancies, the cells' metabolic phenotypes remain elusive. In this study, we observed that liver T-ICs preferentially survived under restricted glucose treatment. These cell populations compete successfully for glucose uptake by preferentially expressing glucose transporters (GLUT1 and GLUT3), whereas inhibition of GLUT1 or GLUT3 abolished the survival advantage and suppressed the tumorigenic potential of liver T-ICs. Among signaling pathways related to T-ICs, IL-6/STAT3 was identified to be responsible for the elevation of glucose uptake in liver T-ICs under glucose limitation. Further investigation revealed that IL-6 stimulation upregulated GLUT1 and GLUT3 expressions in CD133 + cells, particularly during glucose deprivation. More importantly, inhibition of glucose uptake sensitized liver T-ICs to sorafenib treatment and enhanced the therapeutic efficacy in vivo . Our findings suggest that blocking IL-6/STAT3-mediated preferential glucose uptake might be exploited for novel therapeutic targets during hepatocellular carcinoma (HCC) progression. Highlights: Number of putative liver T-ICs are enriched by glucose starvation. T-IC properties are affected by glucose uptake and potentially mediated by a IL6/STAT3-dependent regulation of GLUT1/3. Inhibition of glucose uptake sensitizes liver T-ICs to sorafenib.